Project Report on Automated Accident Prevention by Counting Human Error - VINAY S, ANIL MAHALA, KASHIF and SOURAV SAHA (2012)
INTERNAL GUIDE: MEGHA JESS MATHEW, MVJCE
Keywords: Automated Accident Prevention